Quality and accuracy of online nutrition-related information: a systematic review of content analysis studies - Emily Denniss; Rebecca Lindberg; Sarah A McNaughton (Cambridge University Press, 2023)
Abstract Objective: This systematic review aimed to summarise the level of quality and accuracy of nutrition-related information on websites and social media and determine if quality and accuracy varied between websites and social media or publishers of information. Design: This systematic review was registered with PROSPERO (CRD42021224277). CINAHL, MEDLINE, Embase, Global Health and Academic Search Complete were systematically searched on 15 January 2021 to identify content analysis studies, published in English after 1989, that evaluated the quality and/or accuracy of nutrition-related information published on websites or social media. A coding framework was used to classify studies' findings about information quality and/or accuracy as poor, good, moderate or varied. The Academy of Nutrition and Dietetics Quality Criteria Checklist was used to assess the risk of bias. Setting: N/A. Participants: N/A. Results: From 10 482 articles retrieved, sixty-four were included. Most studies evaluated information from websites (n 53, 82·8 %). Similar numbers of studies assessed quality (n 41, 64·1 %) and accuracy (n 47, 73·4 %). Almost half of the studies reported that quality (n 20, 48·8 %) or accuracy (n 23, 48·9 %) was low. Quality and accuracy of information were similar on social media and websites, however, varied between information publishers. High risk of bias in sample selection and quality or accuracy evaluations was a common limitation. Conclusion: Online nutrition-related information is often inaccurate and of low quality. Consumers seeking information online are at risk of being misinformed. More action is needed to improve the public's eHealth and media literacy and the reliability of online nutrition-related information.